PENERAPAN MODEL KOOPERATIF LEARNING TIPE NHT (NUMBER HEAD TOGETHER) BERBANTUAN MEDIA VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS II SEKOLAH DASAR - Saskia Chairunnisa Kurnia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the results of observations which show that the learning outcomes of students are still low. To respond to this, the researchers conducted Classroom Action Research (PTK) entitled the application of the NHT (Number Head Together) cooperative learning model assisted by instructional video media to improve learning outcomes for class II elementary school students. The objectives to be achieved in this study include: to find out the implementation of the NHT type cooperative learning model assisted by learning video media, to determine the increase in student learning outcomes after being given the NHT type cooperative learning model assisted by learning video media. This research is a class action research with the Kemmis and Mc Taggart. This research was conducted in class II SDN 013 Pasirkaliki with 26 students. This study measures the cognitive learning outcomes of students. The collected data were analyzed using descriptive statistical analysis and the research results from each cycle there was an increase, cycle I obtained a percentage of 64.76% in cycle II increased to 78.57%. it can be concluded that the application of the cooperative learning model of the NHT type assisted by learning video media can improve student learning outcomes. Keywords: Classroom Action Research, Cooperative Learning, learning outcomes.